2014
DOI: 10.1111/1469-0691.12420
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetically related, clinically different: human papillomaviruses 6 and 11 variants distribution in genital warts and in laryngeal papillomatosis

Abstract: Genital warts (GWs) and laryngeal papillomatosis (LP) are two usually benign pathologies related to infection with human papillomaviruses (HPVs), mainly HPV6 and HPV11. The aim of this work was to describe the genetic diversity of HPV6 and HPV11 isolates found in GWs and LPs, and to analyse the differential involvement of viral variants in either lesion. A total of 231 samples diagnosed as GWs (n = 198) or LP (n = 33) and caused by HPV6 or HPV11 monoinfections were analysed. The phylogenetic relationships of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
1
10
1
5
Order By: Relevance
“…In addition, lineage A consisted of four sublineages, A1, A2, A3, and A4, with sublineages A3 and A4 being identified for the first time in this study. Due to the identification of a novel lineage B, originating from a single African isolate, the calculated maximum pairwise dissimilarly of the complete HPV11 genome variants (e.g., isolate LT4 versus isolate SA3408) reached 1.3%, exceeding the previously reported rate of diversity by approximately 4-fold (25,26,28). Hence, the genomic diversity of HPV11 of 1.3% is highly similar to that of its closest relative, HPV6 (1.6%) (29).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…In addition, lineage A consisted of four sublineages, A1, A2, A3, and A4, with sublineages A3 and A4 being identified for the first time in this study. Due to the identification of a novel lineage B, originating from a single African isolate, the calculated maximum pairwise dissimilarly of the complete HPV11 genome variants (e.g., isolate LT4 versus isolate SA3408) reached 1.3%, exceeding the previously reported rate of diversity by approximately 4-fold (25,26,28). Hence, the genomic diversity of HPV11 of 1.3% is highly similar to that of its closest relative, HPV6 (1.6%) (29).…”
Section: Discussionmentioning
confidence: 72%
“…For the purpose of this study, a total of 207 HPV11 isolates were collected from 14 countries covering six continents, and four genomic regions, including the E5a, E5b, and L1 ORFs and the noncoding region URR were sequenced. These particular regions were selected for initial sequencing on the basis of findings from previous studies: (i) E5a, L1, and URR contain sequence information sufficient for unambiguous differentiation between HPV11 sublineages A1 and A2 (25,26,28); (ii) the E5a and E5b genes evolve faster and mutate more frequently than other HPV genes (40,41); and (iii) our recent genomic diversity study of HPV6 (the closest relative of HPV11) showed that the concatenated E5a-E5b-L1-URR sequence can be reliably used as a surrogate for the whole-genome phylogenetic clustering of HPV6 variants (29), and thus, sequencing of the same genomic regions would additionally allow comparison of the genetic diversity of a large number of HPV6 and HPV11 isolates. The genomes of a total of 30 HPV11 isolates showing the highest diversity in the E5a, E5b, L1, and/or URR genomic region were fully sequenced and phylogenetically evaluated together with 48 complete HPV11 genome sequences from GenBank and PaVE, of which 70.1% (34/48) mainly originated from two pre-FIG 1 HPV11 heat map and maximum likelihood trees inferred from 78 complete HPV11 genomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples were processed as previously described [11]. Briefly, total DNA was obtained by proteinase K incubation.…”
Section: Genotypingmentioning
confidence: 99%